Doctors Have no Right to Refuse Medical Assistance in Dying, Abortion or Contraception - Savulescu, Julian; Schuklenk, Udo (Bioethics, 2017)
In an article in this journal, Christopher Cowley argues that we have ‘misunderstood the special nature of medicine, and have misunderstood the motivations of the conscientious objectors’. We have not. It is Cowley who has misunderstood the role of personal values in the profession of medicine. We argue that there should be better protections for patients from doctors' personal values and there should be more severe restrictions on the right to conscientious objection, particularly in relation to assisted dying. We argue that eligible patients could be guaranteed access to medical services that are subject to conscientious objections by: (1) removing a right to conscientious objection; (2) selecting candidates into relevant medical specialities or general practice who do not have objections; (3) demonopolizing the provision of these services away from the medical profession.